SERVANT HEARTS: VILLAGE CADRES’ PUBLIC SERVICE MOTIVATION IN INDONESIA’S MENTAL HEALTH CARE - Erna Setijaningrum; Marni Binti Ghazali; Luqman Purwanto (Universitas Airlangga, 2023)
Background: Despite the growing interest in public service motivation (PSM) research, there is a lack of studies that specifically examine the PSM of individuals in nontraditional roles, such as village cadres, in the context of mental health care in low-resource settings. Aims: This study aimed to fill this knowledge gap by exploring how PSM influences the actions and choices of village cadres in providing care for people with mental illness in Indonesia. Methods: An instrumental case study approach was employed to gather data through in-depth interviews with 14 village actors across five regencies in East Java Province, Indonesia. Results: The study’s findings reveal the crucial role of PSM in inspiring village cadres to provide mental health care by showcasing their sense of duty toward the community, program dedication, and compassion for patients, highlighting the correlation between PSM and callings that focuses on serving others. Conclusion: This study provides empirical insights into the intricate ways PSM influences the behavior of village cadres toward people with mental illness in Indonesia, offering valuable knowledge about the motivations of this particular group of public service providers and informing policy decisions and future research in the field of public administration. Keywords: callings, Indonesia, mental health care, public service motivation, village cadres